Edukasi dan Sosialisasi “Pola Hidup bersih dan Sehat” Sebagai Upaya Pencegahan Covid-19 di Mlaten RT 03/RW 03 Kel Jetis Kec. Lamongan Kab. Lamongan - Mokhtar Sayyid; Rita Nataliawati; Fefty Nurul Aini; Rizky Firdatin Nisa (Jurnal DIKMAS, 2020)
The Covid-19 virus has caused many health problems. Covid-19 has infected many humans ranging from small children to adults and has also caused many deaths. The clean and healthy lifestyle program is a form of embodiment to provide learning experiences and create a conducive condition for society and behavior so that they can apply healthy ways of lifein order to maintain, maintain and improve health. Actions taken are preparation, implementation and evaluation. The purpose of this counseling is to increase public awareness of the importance of implementing a healthy and clean lifestyle (PHBS) in order to reduce the spread of Covid-19. The results of this counseling activity are the creation of harmony between communities through mutual cooperation for the sake of cleanliness of the village environment, activities for making places washing hands and distribution of masks accompanied by conducting educational outreach on the importance of carrying out clean and healthy lifestyles, and the formation of cleaner flower gardens. Thus, public awareness arises from these activities so that they can suppress the increase in the spread of Covid-19 and the environment is also kept clean.